Evolutionary history predicts high‐impact invasions by herbivorous insects. Issue 21 (17th October 2019) - Mech, Angela M.; Thomas, Kathryn A.; Marsico, Travis D.; Herms, Daniel A.; Allen, Craig R.; Ayres, Matthew P.; Gandhi, Kamal J. K.; Gurevitch, Jessica; Havill, Nathan P.; Hufbauer, Ruth A.; Liebhold, Andrew M.; Raffa, Kenneth F.; et al.
Abstract: A long‐standing goal of invasion biology is to identify factors driving highly variable impacts of non‐native species. Although hypotheses exist that emphasize the role of evolutionary history (e.g., enemy release hypothesis & defense‐free space hypothesis), predicting the impact of non‐native herbivorous insects has eluded scientists for over a century. Using a census of all 58 non‐native conifer‐specialist insects in North America, we quantified the contribution of over 25 factors that could affect the impact they have on their novel hosts, including insect traits (fecundity, voltinism, native range, etc.), host traits (shade tolerance, growth rate, wood density, etc.), and evolutionary relationships (between native and novel hosts and insects). We discovered that divergence times between native and novel hosts, the shade and drought tolerance of the novel host, and the presence of a coevolved congener on a shared host, were more predictive of impact than the traits of the invading insect. These factors built upon each other to strengthen our ability to predict the risk of a non‐native insect becoming invasive. This research is the first to empirically support historically assumed hypotheses about the importance of evolutionary history as a major driver of impact of non‐native herbivorous insects. Our novel, integrated model predicts whether a non‐native insect not yet present in North America will have a one in 6.5 to a one in 2, 858 chance of causing widespread mortality of a conifer species if established ( R 2 = 0.91) Synthesis and applications . With this advancement, the risk to other conifer host species and regions can be assessed, and regulatory and pest management efforts can be more efficiently prioritized. Abstract : This research is the first to empirically support historically assumed hypotheses about the importance of evolutionary history as a major driver of impact of non‐native herbivorous insects. We discovered that evolutionary history between native and novel hosts, life history traits of the novel host, and the evolutionary relationship between non‐native and coevolved insects on a shared host were more predictive of impact than traits of the invading insect. Our novel, integrated model predicts whether a non‐native insect not yet present in North America will have a one in 6.5 to a one in 2, 858 chance of causing widespread mortality of a conifer species if established.